Evaluating the effects of biogas slurry and biochar as a partial substitute for chemical fertilizers on greenhouse tomato growth, root traits, and yield: a minimum data set approach - Sa, Qinglin; Zheng, Jian; Wang, Yan; Fu, Xuqin; Wu, You; Liu, Aosong (Frontiers in Plant Science, 2025)
Excessive chemical fertilizer application and nutrient-free irrigation have contributed to suboptimal crop performance and declining yields in greenhouse production. This study investigated the effects of biogas slurry combined with biochar as a partial chemical fertilizer substitute on the growth, root traits, and yield of greenhouse tomatoes. Under equal nitrogen, phosphorus, and potassium inputs and irrigation conditions, different biogas slurry replacement ratios were compared, including CF (traditional fertilization control), FR (chemical fertilizers only), BS25 (low biogas slurry ratio), BS50 (moderate biogas slurry ratio), BS75 (high biogas slurry ratio), and BS100 (biogas slurry only), along with their corresponding treatments combined with biochar, namely CF+C, FR+C, BS25+C, BS50+C, BS75+C, and BS100+C. Path analysis was used to explore the causal relationships between the growth quality index (GQI) and the minimum data set (MDS), revealing the dominant factors affecting GQI of greenhouse tomatoes. Results showed that BS75+C had the most pronounced promoting effects on plant height (PH), stem diameter (SD), and root activity (RA), especially during the flowering stage. At this stage, RA significantly increased to 358.94 μg g−1 h−1 in spring and 355.42 μg g−1 h−1 in autumn (P < 0.05). Leaf area (LA), leaf area ratio (LAR), specific leaf area (SLA), and leaf area index (LAI) exhibited a continuous increasing trend throughout the entire tomato growth period. Significant differences in biomass allocation indicators were observed during the flowering and fruiting stages, including root biomass ratio (RBR), stem biomass ratio (SBR), leaf biomass ratio (LBR), and root-to-shoot ratio (RSR) (P < 0.05). The GQI under BS75+C reached 0.669, which was higher than that of the other treatments, and showed a highly significant positive correlation with tomato yield (P < 0.05). The reliability of the MDS-based evaluation system was confirmed, indicating that it effectively captured representative information from the total data set (TDS). Path analysis further showed that RA, SD, and RBR were the key factors influencing GQI. Further multiple linear regression analysis indicated that SD (Beta = 0.559) and RA (Beta = 0.369) had significant direct effects on GQI, while RBR mainly regulated GQI formation through indirect pathways. Overall, BS75+C emerged as a sustainable and efficient soil management strategy, capable of simultaneously improving root development, plant growth, and yield (151,341 kg ha−1) under greenhouse conditions in arid and semi-arid environments. BS25, however, provided the highest economic benefit (672,361.04 yuan ha−1), offering a more cost-effective alternative under current production conditions.